Análise estrutural de vigas treliçadas de aço com mesa de concreto - Trindade, Luiz Gustavo Cruz [UNESP] (2015)
Mixed steel-concrete trusses, very efficient alternatives to overcome large spans, are generally used in commercial and industrial buildings, and railway and road bridges. In many cases, in order to enable the passage of ducts, truss beam type steel-joist must be considered. In this work, the failure capacity and the rupture mode of a simply supported steel-joist truss with 13,6 meters wide, modified warren type, has been determined by an analytical procedure as well as numerical modeling considering both a bi-dimensional linear analysis and a three-dimensional elasto-plastic analysis. In the study, permanent and variable actions have been considered as well as the prescriptions of the Brazilian code, being the results compared to the numerical analysis. It has been verified that for mixed and isolated steel-joist trusses, the diagonal and amounts have presented small values for internal forces and regions next to the support have reached the yielding limit. Despite of that, the mixed action for the mixed trusses has been observed. Besides, the load resistance force design has been verified for both the analytical and numerical analysis, being the bigger displacements computed with the numerical modeling